RANCANG BANGUN SISTEM INVENTARIS ASET SEKOLAH BERBASIS WEB DI SMK N 6 PADANG TERINTEGRASI QR-CODE - Sabrina, Mutiara; Asmara, Delvi; Dwinggo Samala, Agariadne; Irfan, Dedy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
School asset inventory management at SMK Negeri 6 Padang is still carried out conventionally, so that data recording, searching, borrowing, and reporting require a relatively long time and are prone to recording errors. The absence of a physical asset-tracking mechanism and a systematic record of user activity has also made asset supervision less than optimal. This study aims to design and build a web-based school asset inventory system equipped with multi-access, QR Code, and digital audit features at SMK Negeri 6 Padang. The system was developed using the Software Development Life Cycle (SDLC) with the Waterfall model, covering requirement analysis, system design, implementation, testing, deployment, and maintenance, and was built using the Laravel framework with a MySQL database, while functional testing was carried out through Black Box Testing. The results show that the system simplifies asset data recording, location management, borrowing and return transactions, QR Code-based asset tracking, digital audit trails of user activity, and the preparation of inventory reports more quickly and accurately. Black Box Testing results indicate that all 53 functions across five user roles operate as expected without functional errors, achieving a 100% success rate, so that the system is considered feasible to be implemented as a medium for managing school asset inventory at SMK Negeri 6 Padang.